Social status does not predict in-camp integration among egalitarian hunter-gatherer men. (11th October 2021) - Fedurek, Piotr; Aktipis, Athena; Cronk, Lee; Makambi, E Jerryson; Mabulla, Ibrahim; Berbesque, J Colette; Lehmann, Julia
Abstract: In the last few decades, there has been much research regarding the importance of social prestige in shaping the social structure of small-scale societies. While recent studies show that social prestige may have important health consequences, little is known about the extent to which prestige translates into actual in-person interactions and proximity, even though the level of integration into such real-life social networks has been shown to have important health consequences. Here, we determine the extent to which two different domains of social prestige, popularity (being perceived as a friend by others), and hunting reputation (being perceived as a good hunter), translate into GPS-derived in- and out-of-camp proximity networks in a group of egalitarian hunter-gatherer men, the Hadza. We show that popularity and hunting reputation differ in the extent to which they are translated into time spent physically close to each other. Moreover, our findings suggest that in-camp proximity networks, which are commonly applied in studies of small-scale societies, do not show the full picture of Hadza men's social preferences. While men are in camp, neither popularity nor hunting reputation is associated with being central in the proximity network; however, when out of camp, Hadza men who are popular are more integrated in the proximity networks while men with better hunting reputations are less integrated. Overall, our findings suggest that, to fully understand social preferences among hunter-gatherers, both in-camp and out-of-camp proximity networks should be considered. Abstract : Although there has been much research on the effect of both social integration and social status on wellbeing, little is known how these two social domains are related to each other. In this study we show that, among Hadza hunter-gatherer men, being integrated in social networks is more indicative of popularity as a friend than of hunting reputation. This challenges the idea that social prestige based on hunting reputation is vital in building coalitions.